Friends in the mission of God : relationships in four stories of Evangelical mission history - Birdsall, Doug (Regnum mini book series., 2019)
"This is an abridged version of Doug Birdsall's thesis 'Conflict and Collaboration'. It explores four stories of evangelical mission history in the late twentieth century. It takes as its starting point the year 1974, when the historic International Congress on World Evangelization was held in Lausanne, Switzerland. It records the interaction of the Lausanne Movement with the World Evangelical Fellowship (WEF) and continues to tell the story of Lausanne's interaction with the International Fellowship of Evangelical Mission Theologians (INFEMIT), and moves on to the events that led to the formation of the AD 2000 Movement. The narrative concludes in the year 2000, the year in which the AD 2000 Movement came to an end. While it was a time that two respected evangelical leaders Samuel Escobar and John Stott called 'an amazing time in history that produced an experience of glorious unity', it was also a time of conflict. This study will focus on those conflicts, specifically looking at the conflicts that were connected with the Congress in Lausanne."--Publisher